Policy Model for Sustainable Drinking Water Supply System - Yuki Mahardhito Adhitya Wardhana (PT Penjaminan Infrastruktur Indonesia (Persero), 2018)
In RPJMN 2015-2019, the government has aimed to reach a 100% drinking water services coverage throughout Indonesia in 2019. The actual proper drinking water coverage until 2015 was still at 67.7%. This research seeks to formulate a policy model for sustainable drinking water management system. The method of analysis used in this research is the process model method. The results obtained in this study are policy models for sustainable SPAM development that will include the main variables of this system: raw water source, water treatment processes and water distribution.